Generation of heterozygous and homozygous NF1 lines from human-induced pluripotent stem cells using CRISPR/Cas9 to investigate bone defects associated with neurofibromatosis type 1 - Darle, Annabelle; Mahiet, Thibault; Aubin, Déborah; Doyen, Manon; El Kassar, Lina; Parfait, Béatrice; Lemaitre, Gilles; Baldeschi, Christine; Allouche, Jennifer; Holic, Nathalie (Frontiers in Cell and Developmental Biology, 2024)
Neurofibromatosis type 1 is one of the most common genetic disorders caused by heterozygous germline NF1 mutations. NF1 affects many systems, including the skeletal system. To date, no curative therapies are available for the skeletal manifestations such as scoliosis and tibial dysplasia, mainly due to the lack of knowledge on the mechanisms underlying this process. By using CRISPR/Cas9 mediated gene editing in human induced pluripotent stem cells to minimize the variability due to genetic background and epigenetic factors, we generated isogenic heterozygous and homozygous NF1deficient hiPSC lines to investigate the consequences of neurofibromin inactivation on osteoblastic differentiation. Here, we demonstrate that loss of one or both copies of NF1 does not alter the potential of isogenic hiPSCs to differentiate into mesenchymal stem cells (hiPSC-MSCs). However, NF1 (+/-) and NF1 (-/-) hiPSC-MSCs show a defect in osteogenic differentiation and mineralization. In addition, we show that a mono-allelic deletion in NF1 in an isogenic context is sufficient to impair cell differentiation into osteoblasts. Overall, this study highlights the relevance of generating isogenic lines, which may help for genotype-phenotype correlation and provides a human cellular model to understand the molecular mechanisms underlying in NF1 and thus discover new therapeutic strategies.